The use of dermal templates in dermato-surgery and patient perspectives (Dermatology Reports, 2024)
Acellular dermal matrices currently represent a useful reconstructive method in onco-dermatologic surgery. Nevertheless, they have some limitations, especially in terms of costs and outpatient post-operative wound care. While some studies on their cost-tobenefit ratio in breast surgery have already been issued, evidence is currently lacking in onco-dermatological surgery. The aim of this study was to evaluate the clinical outcomes perceived by patients who had undergone onco-dermatologic surgery in which either acellular dermal matrices or skin grafts had been used as reconstructive methods. A study population of 150 patients was identified retrospectively and patients’ degree of satisfaction was assessed through the Global Aesthetic Improvement Scale and the Patient Scar Scale Questionnaire. Despite similar scores among the study groups, slightly better results were appreciable after single- stage grafting. However, to what extent these variations really represent a significant difference from a clinical point of view remains to be determined. Moreover, other potential bias in the interpretation of our results may reside in differences in terms of age, body location and baseline tumor size among the study groups. Therefore, further research is needed.